Design, synthesis, characterization and antimicrobial/antioxidant activities of 1, 4-dicarbonyl-phenyl-dihydrazide based macrocyclic ligand and its Cu(II), Co(II) and Ni(II) complexes. (November 2016) - Gull, Parveez; Dar, Ovas Ahmad; Malik, Manzoor Ahmad; Hashmi, Athar Adil
Abstract: Mononuclear transition metal complexes of Cu(II), Co(II) and Ni(II) with a newly synthesised macrocyclic ligand derived from 1, 4-dicarbonyl-phenyl-dihydrazide and 1, 2-diphenylethane-1, 2-dione (2:2) have been synthesised. The synthesised compounds were characterised by various physical and spectroscopic techniques including elemental analysis, FTIR, Uv–Vis., 1 H NMR, mass spectra, magnetic moment and XRD. The investigation of these macrocyclic complexes established that the stability of metal–ligand coordination through N atoms as tetradentate chelates. The metal/ligands ratio of 1:1 was proposed to afford octahedral geometry for the complexes. The antimicrobial activity of the compounds against some bacterial and fungal species were done by well diffusion method and the results shows that the metal complexes have a promising biological activity comparable with the parent ligand against all bacterial and fungal species. The antioxidant activity of the compounds was also studied through scavenging effect on DPPH radicals with the copper complex showing enhanced activity than other compounds. Additionally, the docking studies predicted the high antimicrobial activity due to the interaction of ligand with the protein. Graphical abstract: Highlights: Preparation of Cu(II), Co(II) and Ni(II) complexes of the new macrocyclic schiff's base ligand. Elemental analysis, spectral characterization of the ligand and its complexes. IR spectrum of the ligand indicates the coordination of the azomethine nitrogen atoms. Antimicrobial activities of the ligand and its complexes, as growth inhibiting agents, have been screened in vitro against different species of bacteria and fungi. Docking studies shows the effective binding of the ligand with the target protein.